Nonpharmacological Management of Postpartum Pain After Cesarean and Vaginal Delivery: A Systematic Review - Muhammad Oliver (Sriwijaya Journal of Medicine, 2026)
Postpartum pain is a common and clinically significant issue following both cesarean and vaginal deliveries, affecting maternal comfort, mobility, breastfeeding, and early mother-infant bonding. While pharmacological analgesics are effective, they carry risks such as gastrointestinal disturbances, sedation, and interference with lactation, prompting interest in nonpharmacological alternatives. This systematic review evaluated randomized controlled trials (RCTs) published between 2015 and 2025 that assessed nonpharmacological interventions for postpartum pain including acupressure, transcutaneous electrical nerve stimulation (TENS), hand and back massage, abdominal binders, cryotherapy, and photobiomodulation. Ten studies were included, comprising 7 cesarean and 3 vaginal delivery trials. Acupressure, TENS, and massage consistently reduced pain scores, enhanced functional recovery, and improved maternal comfort without significant adverse effects, whereas abdominal binder use showed limited benefit. For vaginal deliveries, cryotherapy and photobiomodulation effectively decreased perineal pain and edema. Overall, nonpharmacological interventions were safe, low-cost, and patient-centered, offering meaningful reductions in postpartum pain and improvements in functional outcomes. However, variability in intervention protocols, dosing, and outcome measures limits direct comparisons, highlighting the need for further research to establish standardized approaches and optimize clinical application. These findings support incorporating nonpharmacological strategies as adjuncts or alternatives to pharmacological pain management in postpartum care.